ANTIFUNGAL ACTIVITY OF SELECTED PLANT EXTRACTS AGAINST IMPORTANT SEED BORNE FUNGI OF MAIZE - WAHEGAONKAR NILIMA K.,; SHIRURKAR DEEPAVALI D., (International Journal of Pharma and Bio Sciences, 2013)
Fifteen different plants used in traditional Indian medicine were examined against eight fungal species viz. Aspergillus flavus, Aspergillus niger, Aspergillus terreus, Aspergillus oryzae, Aspergillus fumigatus, Fusarium verticillioides (Synonym F. moniliforme), Fusarium solani and Penicillium sp. using the agar disc diffusion method. The alcoholic extracts of 15 plants exhibited varying degrees of inhibition activity against the above seed borne fungi. Seven of the 15 plants studied had antifungal activity against above listed fungi while the remaining had no antifungal activity. Extent of activity also differed with the part of the plant used.